A comparative study of American ginseng (spp. Panax quinquefolius) and Donepezil on working memory in rats using scopolamine induced disruption of memory - Shende, Shrikrishna S.; Shinde, Kalbhairav M.; Tilak, Abhijit V.; Rane, Bhalachandra T.; Raveendran, Siddhi; Dabhade, Sanjay A. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Treatment of Alzheimer’s disease (AD) includes acetylcholinesterase inhibitors like Donepezil. American ginseng has been postulated to enhance learning and memory owing to its antiapoptotic activity as well as inhibition of formation of β amyloid plaque. Scarce data is available on effect of combination of these two drugs. Hence, we have conducted this study to evaluate the same. Aim and objectives of the study were to evaluate the role of American ginseng on working memory in rats and to compare the effect of American ginseng with Donepezil on working memory in rats. Methods: Sprague-Dawley rats of either sex, weighing 150-200g were used and obtained from animal house of Dr. D. Y. Patil Medical College, Hospital and Research Centre, Pimpri, Pune. To study the effects of the drugs on working memory in rats, they were trained for conditioned avoidance response (CAR) using Cook's pole climbing apparatus. The method of Fellow and Cook was used. Results: In the group C (i.e. the control group), 50% of rats showed the retention of CAR. In the group S (i.e. only scopolamine group), only 20% of rats showed the retention of CAR. In the group S+AG (i.e. scopolamine and American ginseng), 60% of rats showed the retention of CAR. In the group S+ D (i.e. scopolamine and Donepezil) 70% of rats showed retention of CAR. In the group S+D+AG (i.e. the combination group of scopolamine, Donepezil and American ginseng), 80% of rats showed the retention of CAR. Conclusions: From this study we can conclude that American ginseng and Donepezil have comparable effects in retention of working memory. The combination of American ginseng and Donepezil can have additive effect on the retention of working memory.